Unidade de ensino potencialmente significativa norteada por metodologias ativas: uma proposta para o estudo de gases ideais na disciplina de física no ensino médio - Sousa, Rejane Rodrigues de Oliveira (Universidade Federal Rural do Semi-Árido, 2020)
The school, as a social space and environment developed for production of systematized knowledge, cannot be aligned with the idea of teaching practices that do not corroborate with the expectations of an increasingly dynamic society. In this sense, is required a new pedagogical approach which reaches the students' aspiration. Faced with this reality, rises the care and desire to carry out this work, where we expose the elaboration, application and evaluation of a didactic sequence for the study of gases with students of the 2nd grade of high school in the state school system. The didactic sequence is under the assumptions of the Significant Learning Theory by the North American David Ausubel as a way to overcome old practices, leading the study of Physics closer to the students' reality. The didactic sequence, called Potentially Significant Teaching Unit, consists of pre and post tests, introductory text, questionnaire, concept maps, video lessons and problem situations (stations) in accordance with the development of competencies and skills brought by the Parâmetros Curriculares Nacionais(PCN and PCN +) and the Base NAcional Comum Curricular (BNCC). Active methodologies guide this work by favoring the strengthening of autonomy, the inverted classroom allows the student to realize that the production of knowledge can occur in another bias, when there is an inversion of what is done in the classroom to be done at home. Collaborative activities promote an environment for the negotiation of ideas, meanings and concepts. This work is a qualitative, quantitative and experimental character, as it is a teaching experiment, theoretically based on works and researches by Ausubel (1963, 1968); Moreira (2000, 2002, 2011); Freire (2005); Brazil (1999); Brazil (2002); Reeve (2009); Coelho (2018); Morin (2000); Moran (2015), “Cobb and Steffe (1983) among others. We found that the results of the Potentially Significant Teaching Unit corroborate the theoretical assumptions that underlie this research. The analysis of the results of a qualitative and experimental nature thappend through the positioning of students, the evolution of conceptual maps and individual and summative evaluations. As for the results of a qualitative nature, we follow the parameters of Hake's Gain. Thus, we infer that it is possible for a classroom practice guided by active methodologies to positively influence the significant learning of Physics. Therefore, capacitating the teacher to use practices that develop in students autonomy and intellectual ability to understand and solve real situations, can contribute significantly to the process of teaching and learning
Keywords: Ensino de Física; UEPS; Aprendizagem Significativa; Metodologias Ativas; Physics Teaching; UEPS; Meaningful Learning; Actives Methodologies; MULTIDISCIPLINAR::ENSINO